Improving Students’ Collaboration Thinking Skill Under the Implementation of the Quantum Teaching Model - Nahar, Syamsu; Suhendri, Suhendri; Zailani, Zailani; Hardivizon, Hardivizon (International Journal of Instruction, 2022)
Students' collaborative thinking skills in the elementary schools still need attention to be improved. Most elementary school students have difficulty in cultivating this skill. Even though, this skill is one of the 21st century skills, namely 4C (creative thinking skill, critical thinking skill, communication skill and collaborative thinking skill). This study aims to improve the students collaboration thinking skills under the implementation of a cooperative learning type, namely a quantum teaching model. This research was conducted by using quasi experiment in the form of non-equivalent (pre-test and post-test) control group design. The sample in this study were students of the Integrated Islamic Elementary School, Al-Musabbihin, Medan City, totaling 55 students. To test the difference of the students' collaborative thinking skills in the control class and experiment class under the implementation of quantum teaching model, we used statistics analysis tools, namely homogeneity test and independent sample t-test. The results of Levene Statistic for homogeneity test showed a significance value of 0.762 > 0.05, which means the two classes are homogeneous. The independent sample "t-test" showed that the score is 0.007 < 0.05, which implies the difference between the two classes is significant. It concludes that the implementation of quantum teaching model can improve the students' collaboration thinking skills in Islamic Religious Education Learning. Therefore, increasing the teachers skills in developing quantum teaching learning materials needs to be improved simultaneously through government policy programs or independently through deliberation activities for teachers of Islamic religious education subjects.